2010
DOI: 10.1121/1.3327799
|View full text |Cite
|
Sign up to set email alerts
|

Physically constrained maximum likelihood mode filtering

Abstract: Mode filtering is most commonly implemented using the sampled mode shapes or pseudoinverse algorithms. Buck et al. ͓J. Acoust. Soc. Am. 103, 1813-1824 ͑1998͔͒ placed these techniques in the context of a broader maximum a posteriori ͑MAP͒ framework. However, the MAP algorithm requires that the signal and noise statistics be known a priori. Adaptive array processing algorithms are candidates for improving performance without the need for a priori signal and noise statistics. A variant of the physically constrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…7 Mode filters are generally linear estimators in the form d ¼ Hp. Among the most common choices for H, we find, 4,5 • The matched filter (MF) H MF ¼ W H , where H denotes conjugate transpose.…”
Section: The Normal Mode Modelmentioning
confidence: 99%
“…7 Mode filters are generally linear estimators in the form d ¼ Hp. Among the most common choices for H, we find, 4,5 • The matched filter (MF) H MF ¼ W H , where H denotes conjugate transpose.…”
Section: The Normal Mode Modelmentioning
confidence: 99%
“…Papp et al [4], [5] applied this idea to mode processing in the application of underwater acoustic communications. They showed that it is possible to use mode filtering to improve array processing.…”
Section: Introductionmentioning
confidence: 98%
“…Various methods can be employed to handle limited sample availability, including the use of application-specific physical constraints, e.g., [97], [132]. However, the most widespread general purpose methods are regularization-based.…”
Section: The Sample Limited Regimementioning
confidence: 99%